2000
DOI: 10.2135/cropsci2000.404923x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Endophyte‐Infected Cool‐Season Grasses to Environmental Stresses: Mechanisms of Drought and Mineral Stress Tolerance

Abstract: Cool‐season grasses infected with Neotyphodium spp. endophytes have an extraordinary impact on the ecology and economy of pasture and turf. A range of adaptations of endophyte‐infected grasses to biotic and abiotic stresses has been identified but mechanisms of these adaptations are not clearly understood. In this review, we present recent research progress on endophyte‐related mechanisms affecting abiotic (drought, mineral) and selected aspects of biotic stress tolerance in cool‐season grasses. Endophytes ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
469
3
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 713 publications
(510 citation statements)
references
References 159 publications
17
469
3
7
Order By: Relevance
“…In contrast, other experiments showed that the amount of ergot alkaloids translocated to roots is very small, and experiments with Neotyphodium knockout mutants having their pathway of ergot alkaloid synthesis disrupted suggested that these alkaloids are not responsible for the inhibition of nematode populations in endophyte infected plants (Panaccione et al, 2006). Nevertheless, other types of alkaloids with antiherbivore activity are produced by Neotyphodium species, and chemical changes such as the production of phenolic compounds do occur in Neotyphodium-infected roots (Malinowski and Belesky, 2000). In conclusion, Neotyphodium endophytes provide host plants with protection against several nematode species, but the mechanism of action underlying this process is still unknown.…”
Section: Interactions With Nematodesmentioning
confidence: 99%
“…In contrast, other experiments showed that the amount of ergot alkaloids translocated to roots is very small, and experiments with Neotyphodium knockout mutants having their pathway of ergot alkaloid synthesis disrupted suggested that these alkaloids are not responsible for the inhibition of nematode populations in endophyte infected plants (Panaccione et al, 2006). Nevertheless, other types of alkaloids with antiherbivore activity are produced by Neotyphodium species, and chemical changes such as the production of phenolic compounds do occur in Neotyphodium-infected roots (Malinowski and Belesky, 2000). In conclusion, Neotyphodium endophytes provide host plants with protection against several nematode species, but the mechanism of action underlying this process is still unknown.…”
Section: Interactions With Nematodesmentioning
confidence: 99%
“…Parasitic, saprophytic and pathogenic fungi can be very deleterious to a plant, while endophytes and mycorrhizal fungi are considered beneficial symbionts which promote plant growth, confer enhanced resistance to various pathogens and pests, and improve survival under unfavorable environmental conditions [4] [5] [25] (reviewed in [56]). Several endophytes identified in this study have previously been shown to promote plant growth under normal and/or stressed conditions.…”
Section: Potential Of Fungal Endophytes Collected In This Studymentioning
confidence: 99%
“…It was suggested by Malinowski & Belesky (2000) that tall fescue cultivars containing novel endophytes have a wider zone of adaptation than endophyte-free cultivars and are more drought tolerant. This may enable novel endophyte cultivars of tall fescue to be used in rainfall zones that are marginal for endophyte-free cultivars.…”
Section: Endophytesmentioning
confidence: 99%